Some biological parameters of brinjal shoot and fruit borer, Leucinodes orbonalis guenee (lepidoptera: pyralidae) on potato in laboratory condition (Bangladesh Journal of Agricultural Research, 2015)
Studies were made on the biology of brinjal shoot and fruit borer (BSFB), Leucinodes orbonalis Guenee feeding on peeled potato tubers as host in the laboratory. It was observed that moths were active at night for mating, oviposition and adult emergence. Adult emergence started just after sunset and it was maximum (88.90%) during the first half of the night. Maximum mating occurred at late night where 90.80% mating occurred in the first night of adult emergence. Oviposition occurred in the second night of emergence when 86.62% of eggs were deposited during the first half of the night. A female laid 288.05 eggs in 2.65 days in summer and 185.55 eggs in 2.70 days in winter. The egg hatching and larval and pupal period of BSFB were 4.13, 10.40 and 6.60 days, respectively in summer and 6.90, 14.50 and 10.65 days in winter. BSFB needs 10.40 and 14.50 days to complete its larval period in summer and winter, respectively. Pupal period lasted for 5-13 days. Life cycle from egg to adult was 17-44 days. The longevity of male and female adult was 3.50 and 6.20 days in summer and 4.85 and 8.90 days in winter. Temperature in two seasons showed variations in the biology of BSFB.Bangladesh J. Agril. Res. 40(3): 381-390, September 2015